The mechanics and physics of high-speed dislocations: a critical review. (19th May 2021) - Gurrutxaga–Lerma, Beñat; Verschueren, Jonas; Sutton, Adrian P.; Dini, Daniele
ABSTRACT: High speed dislocations have long been identified as the dominant feature governing the plastic response of crystalline materials subjected to high strain rates, controlling deformation and failure in industrial processes such as machining, laser shock peening, punching, drilling, crashworthiness, foreign object damage, etc. Despite decades of study, the role high speed dislocations have on the materials response remains elusive. This article reviews both experimental and theoretical efforts made to address this issue in a systematic way. The lack of experimental evidence and direct observation of high speed dislocations means that most work on the matter is rooted on theory and simulations. This article offers a critical review of the competing theoretical accounts of high speed mechanisms, their underlying hypothesis, insights, and shortcomings, with particular focus on elastic continuum and atomistic levels. The article closes with an overview of the current state of the art and suggestions for key developments in future research.